Pencegahan Dan Penanggulangan Covid-19 Di Tempat Kerja - Zulfikar, Zulfikar; Yuliana, Lina; Setyawati, Nur Falah (Program Studi D4 K3 Universitas Balikpapan, 2022)
Coronaviruses are a large family of viruses that cause disease. There are at least two types of coronavirus that cause diseases that cause severe symptoms such as Middle East Respiratory Syndrome (MERS) and Severe Acute Respiratory Syndrome (SARS). The total number of confirmed COVID-19 cases globally is 108,684,743 with 2,399,103 deaths. Cases in Indonesia were recorded to be contaminated with 1,233,959 cases with 33,596 deaths. Corona viruses are a group of related RNA viruses infecting animals that cause disease in mammals and birds. In humans, this virus attacks the respiratory system and causes infections in the respiratory tract. Corona virus can cause mild disorders of the respiratory system, lung infections and can cause death. The targets in this activity are to provide an understanding of the implementation of the covid-19 health protocol in the workplace, to provide an understanding to the general public about the dangers and risks of covid-19.